Division of Parent Care Among Adult Children. (28th December 2019) - Lin, I-Fen; Wolf, Douglas A
Abstract: Objectives: Many older adults rely on their children's support to sustain community residence. Although filial norms encourage adult children to help their parents, not every child provides parent care in times of need. The majority of prior studies have adopted an individualistic perspective to examine factors associated with individual children's caregiving behavior. This study complements previous work by using the family systems perspective to understand how caregiving responsibilities are allocated among children in the family and how the pattern of care division evolves over time. Method: Data came from seven rounds of the National Health and Aging Trends Study (2011–2017), in which community-dwelling respondents were asked about all of their children and which children provided them with care. Multilevel models were estimated to examine how caregiving responsibilities were distributed among children and how the children's caregiving efforts responded to changes in their parents' frailty. Results: About three quarters of older adults reported receiving help from only one child, and the average of monthly care hours was about 50 at baseline. As parents' frailty increased, the proportion of children providing parents rose and the allocation of parent-care hours became more equal. Discussion: This study underscores the importance of using the family systems perspective to better understand adult children's caregiving behavior. Although just one adult child providing care is the most common caregiving arrangement initially, adult children tend to work with their siblings to support parents' aging in place as parents' need for care increases.